2021
DOI: 10.1021/acs.jafc.1c04289
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery of Green Biomass─How to Extract and Evaluate High Quality Leaf Protein for Food?

Abstract: There is a growing need for protein for both feed and food in order to meet future demands. It is imperative to explore and utilize novel protein sources such as protein from leafy plant material, which contains high amounts of the enzyme ribulose-1,5-biphosphate carboxylase/oxygenase (RuBisCo). Leafy crops such as grasses and legumes can in humid climate produce high protein yields in a sustainable way when compared with many traditional seed protein crops. Despite this, very little RuBisCo is utilized for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 189 publications
0
42
0
Order By: Relevance
“…Therefore, strategies are needed to sophisticate the protein extraction, filtration, and fractionation to improve the quality and usability of protein fractions. Recently, a green leaf biorefinery utilizes a promising membrane filtration technology that includes several fractionation steps and avoids usage of chemicals resulting in higher protein quality with potential for food applications. , However, so far the method has been focused on optimizing protein quality and concentration, and the effect on ANFs has not been investigated.…”
Section: Other Methods and Future Directionsmentioning
confidence: 99%
“…Therefore, strategies are needed to sophisticate the protein extraction, filtration, and fractionation to improve the quality and usability of protein fractions. Recently, a green leaf biorefinery utilizes a promising membrane filtration technology that includes several fractionation steps and avoids usage of chemicals resulting in higher protein quality with potential for food applications. , However, so far the method has been focused on optimizing protein quality and concentration, and the effect on ANFs has not been investigated.…”
Section: Other Methods and Future Directionsmentioning
confidence: 99%
“…When compared with ovalbumin, alfalfa leaf protein showed higher foam capacity but foam stability tends to be lower (Wang & Kinsella, 1976). In contrast, another study conducted by Knuckles reported higher foam stability for alfalfa LPC compared to egg white protein, and better foam stability might have resulted because the LPC was a more purified white fraction (Knuckles & Kohler, 1982;Møller et al, 2021). For alfalfa protein, it was reported that the presence of lipids (∼12%) in their composition has some negative effects on their foam stability (Wang & Kinsella, 1976).…”
Section: Foaming Propertymentioning
confidence: 98%
“…Different anti-nutritional factors are present in different plant species and they need to be quantified in each specific case as they may concentrate in the protein fraction and affect nutrient bioavailability. Any new protein product produced from alfalfa, clover or grass needs an EFSA approval before the protein can be used in food products in the EU (Møller et al, 2021).…”
Section: Possibilities For Using the Protein In Human Foodmentioning
confidence: 99%